Tropylium salts as efficient organic Lewis acid catalysts for acetalization and transacetalization reactions in batch and flow. Issue 17 (21st June 2017) - Lyons, D. J. M.; Crocker, R. D.; Enders, D.; Nguyen, T. V.
Abstract : Tropylium salts were reported as organic-Lewis acids to efficiently catalyze acetalization reactions in batch and flow. Abstract : Acetalization reactions play significant roles in the synthetically important masking chemistry of carbonyl compounds. Herein we demonstrate for the first time that tropylium salts can act as organic Lewis acid catalysts to facilitate acetalization and transacetalization reactions of a wide range of aldehyde substrates. This metal-free method works efficiently in both batch and flow conditions, prompting further future applications of tropylium organocatalysts in green synthesis.